Preparation method for heterogeneous gradient material

By preparing the heterogeneous gradient material Cr-Ti-Mg-Ni-Cu on the surface of titanium alloy rods or pipes, the problem of interlayer cracks of layered functional gradient materials is solved by using high injection speed and plasma sintering technology, and a heterogeneous layered structure with high connection strength and heat/wear resistance is achieved.

CN119897468APending Publication Date: 2025-04-29AVIC BEIJING INST OF AERONAUTICAL MATERIALS +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411500246.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Laminated functional gradient materials cause interlayer cracks due to differences in the physical and chemical properties of the material, which in turn causes mechanical failures.

Method used

A preparation method is adopted to prepare the heterogeneous gradient material Cr-Ti-Mg-Ni-Cu on the surface of titanium alloy rod or pipe, and use high injection speed and plasma sintering technology to achieve mechanical pinning and curing of the material to form a heterogeneous layered structure.

Benefits of technology

By this method, the prepared heterogeneous gradient material layers have high connection strength, reducing the risk of cracks, improving the integrity of the component and heat/wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897468A_ABST
    Figure CN119897468A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method for a heterogeneous gradient material, a device used in the method comprises a base station (1) playing a supporting role, the base station (1) fixes a metal part (6) through a rotating shaft (2) and can drive the metal part (6) to rotate along the central axis of the metal part (6), a heating sleeve (3) is arranged around the metal part (6), and the heating sleeve (3) is used for heating the metal part (6). A channel (4) is machined in the heating sleeve (3) and used for inputting gradient materials (5) of different phases and process gas, the channel (4) is communicated with the atmosphere, and the gap between the inner wall of the heating sleeve (3) and the outer surface of the metal part (6) is 1 / 3-1 / 2 of the maximum rotating radius of the metal part (6). The method is prepared on the basis of a heterogeneous gradient material Cr-Ti-Mg-Ni-Cu, each layer of the gradient material is subjected to an interface reaction, the interface is not a straight line but is in grinding tooth-shaped coupling, each layer is heterogeneous, the connection strength of each layer is high, cracks are not likely to be generated, and the integrity of the component is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a preparation method for heterogeneous gradient materials, belonging to the technical field of heat dissipation component processing and manufacturing. Background Art

[0002] Functionally graded materials are generally classified into two types, homogeneous (where the material is uniformly distributed throughout the volume) and heterogeneous (layered, where the various materials are interconnected at specific boundaries where they touch). An important issue facing layered functionally graded materials is interlayer cracking due to differences in the physicochemical properties of the bonded materials, which in turn leads to mechanical failure.

[0003] According to the Russian Science website: The Russian Far Eastern Federal University has cooperated to develop a method for preparing functional gradient materials for aircraft engines, and obtained a heterogeneous (layered) functional gradient material based on the connecting metal Cr-Ti-Fe-Co-Ni-Cu. The new technology will improve the manufacturing efficiency of components with gradient functional characteristics, thereby improving the quality of aircraft engines. In addition, NASA's Langley Research Center has developed a method for large-scale manufacturing of composite components with high reliability and the ability to maintain predictable mechanical and material properties. This technology is achieved by using a new barrier layer composed of epoxy resin / prepreg material, which not only has the advantages of co-curing process to connect large and complex composite structures, but also does not require redundant fasteners, thereby reducing assembly time and cost. However, the specific process route has not been reported. Summary of the invention

[0004] The technical solution of the present invention is based on the above-mentioned foreign research background and is designed in response to the existing technical conditions to provide a preparation method that can be used for heterogeneous gradient materials. Its purpose is to prepare a layer of heterogeneous gradient material on the outer surface of titanium alloy rods / tubes used as rotating body components to improve the heat / wear resistance of the titanium alloy surface.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] The device used in the preparation method of the heterogeneous gradient material includes a base 1 for supporting, the base 1 fixes a metal part 6 through a rotating shaft 2 and can drive the metal part 6 to rotate along its central axis, a heating sleeve 3 is arranged around the metal part 6, a channel 4 is processed on the heating sleeve 3 for inputting gradient materials 5 of different phases and process gases, the channel 4 is connected to the atmosphere, and the gap between the inner wall of the heating sleeve 3 and the outer surface of the metal part 6 is 1 / 3 to 1 / 2 of the maximum rotation radius of the metal part 6;

[0007] The steps of the preparation method are as follows:

[0008] Step 1: Preparation of metal parts 6 and gradient material 5

[0009] The metal part 6 is a titanium alloy rod or tube, and the surface of the metal part 6 is machined to make its surface roughness not greater than 1.6; Cr powder, Ti powder, Mg powder, Ni powder and Cu powder are prepared as gradient material 5, and the metal powder particle size is -350 mesh to -450 mesh, and the purity is 99.99%; hydrogen and helium are prepared as process gases, and the gas purity is 99.99%;

[0010] Step 2: Preheating of metal parts 6

[0011] Start the heating sleeve 3, raise the temperature to 500-700°C, and preheat the metal part 6. The preheating makes the surface of the metal part 6 red and sticky. Combined with the low roughness of the surface of the metal part 6, favorable conditions are formed for the subsequent attachment and mechanical pinning of the gradient material 5 on the low-smoothness surface of the metal part 6. At the same time, the metal part 6 starts to rotate at a speed of 10-20rad / s. This high speed of rotation can ensure that the temperature field of the metal part 6 is more uniform. The metal part 6 starts to keep warm while rotating, and the insulation time is 1h-2h. Then the rotation speed is reduced to 5-10rad / s. This speed makes the tangential speed of the gradient material 5 on the surface of the metal part 6 lower when it is attached and mechanically pinned, and prepares for the subsequent laying of the gradient material 5 powder;

[0012] Step 3: Laying the first layer of gradient material 5

[0013] The rotation speed of the metal part 6 is maintained, and Cr powder is sprayed onto the surface of the metal part 6 through the channel 4 at a spray rate of 70-100 mm / s. At this time, the Cr powder particles impact the surface of the metal part 6 at a relatively high speed and are pinned and fixed. When the Cr powder is laid to a thickness of 0.5-1.5 mm, the spraying is stopped, and the heating is stopped at the same time. The rotation speed of the metal part 6 is reduced to 1-5 rad / s, and helium is input into the heating sleeve 3 through the channel 4 to help the metal part 6 cool down. After that, the rotation speed of the metal part 6 is increased by 0.5-1 rad / s for every 50°C decrease in the temperature in the heating sleeve 3 until it is reduced to room temperature. During this process, the metal part 6 and the Cr powder layer on its surface shrink, causing the Cr powder particles that are not firmly pinned to fall off. In the process of increasing the rotation speed, the Cr powder particles that are not firmly pinned to fall off further, thereby preparing for the next secondary pinning operation;

[0014] After the temperature of the metal part 6 drops to room temperature, check the thickness of the Cr powder layer, and repeat the above operation process again until the Cr powder laying thickness reaches 0.5-1.5mm after the metal part 6 cools to room temperature;

[0015] Step 4: Solidification of the first layer of gradient material 5

[0016] The heating jacket 3 is started, and the temperature is raised to 600-1200°C, and the Cr powder layer on the surface of the metal part 6 is plasma sintered. At the same time, hydrogen is transported into the heating jacket 3 through the channel 4 at a pressure of 2-3 atmospheres. After the hydrogenation process is maintained for 0.5-1h, the metal part 6 is cooled to room temperature, and the pressure of the heating jacket 3 is restored to the atmospheric pressure level. At this time, the Cr powder layer has a porosity of 20-30%;

[0017] Step 5: Laying and curing the second to fifth layers of gradient material 5

[0018] Repeat steps 3 to 4 to sequentially complete the laying and solidification of Ti powder, Mg powder, Ni powder, and Cu powder, and then sequentially form a Cr-Ti-Mg-Ni-Cu heterogeneous layered structure on the surface of the metal part 6, wherein the layers of the layered structure have transition phases that intersect and adhere to each other;

[0019] Step 6: Heterogeneous layered structure deformation

[0020] An electric pulse power source is connected to both ends of the metal part 6 to heat the metal part 6 to 800-1200°C for plasma sintering. At the same time, the metal part 6 starts to rotate at a speed of 5-10 rad / s for 2-4 hours, and argon gas is supplied into the heating sleeve 3 at a pressure of 5-10 atmospheres. After dehydrogenation, the rotation and heating are stopped and the metal part is cooled to room temperature to obtain a titanium alloy rod or tube having a non-homogeneous gradient material Cr-Ti-Mg-Ni-Cu on the surface, and the microstructure is nano-sized and the grain boundaries are broken.

[0021] In addition, the part 6 is a titanium alloy rod or tube, and the base 1 is fixed from both ends of the titanium alloy rod or tube through the rotating shaft 2 and drives it to rotate.

[0022] The characteristics and beneficial effects of the technical solution of the present invention are as follows:

[0023] 1. The present invention designs a method for preparing a non-homogeneous gradient material Cr-Ti-Mg-Ni-Cu based on a metal material matrix. The obtained non-homogeneous gradient material Cr-Ti-Mg-Ni-Cu has an interface reaction in each layer of the gradient material, and the interface is not a straight line, but a meshing coupling. Each layer is non-homogeneous, and the connection strength of each layer is high, and cracks are not likely to occur, thereby ensuring the integrity of the component;

[0024] 2. The heterogeneous gradient material Cr-Ti-Mg-Ni-Cu based on the metal material matrix prepared by the scheme of the present invention is firstly subjected to a certain temperature to make the metal particles easy to adhere to the surface, and then the metal particles are mechanically pinned with the matrix / the upper layer material by using a high injection speed, and then the gradient material is initially solidified by plasma sintering, and finally, micro-deformation and complete solidification are achieved by the temperature difference generated by the heat source from the inside to the outside of the matrix and the heat source from the outside to the inside, as well as the gas pressure;

[0025] 3. Through the scheme of the present invention, each layer of the gradient material Cr-Ti-Mg-Ni-Cu is heterogeneous. This is mainly because, first, the laying of each layer of material is completed by high-flow gas. During this process, plastic deformation will occur between the layers of material, and the harder powder particles will be embedded in the softer powder particles, and the harder powder particles will be broken. Second, after each layer of material is laid, plasma sintering is carried out in situ. Under the action of hydrogen, some powder particles will also undergo hydrogenation and dehydrogenation reactions, causing decomposition inside the powder particles, refinement of the microstructure, and a more complex interface. Third, during repeated laying and sintering, through temperature adjustment, the phase components generated by interface reactions at different positions are also different, resulting in the heterogeneity of each layer of the gradient material Cr-Ti-Mg-Ni-Cu.

[0026] 4. The micro-deformation process designed by the present invention ensures that the heterogeneous gradient material Cr-Ti-Mg-Ni-Cu based on the metal material matrix is ​​completely solidified, mainly by utilizing the temperature difference between the upper and lower surfaces of the material to promote internal heat transfer of the material. Combined with the hydrogen pressure, the microstructure is nano-sized, the grain boundary migration is increased, and the interface reaction is promoted;

[0027] 5. Through the scheme of the present invention, the preparation of the heterogeneous gradient material Cr-Ti-Mg-Ni-Cu based on the metal material matrix can be achieved by simply adjusting the gas pressure, the matrix rotation speed and the matrix temperature field distribution, without the aid of adhesives, the efficiency is significantly improved, and it can be used to prepare large-scale components. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A schematic diagram of a device used in the technical solution of the present invention DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments:

[0030] See attached Figure 1As shown, the device used in the preparation method of the heterogeneous gradient material includes a base 1 for supporting, the base 1 fixes a metal part 6 through a rotating shaft 2 and can drive the metal part 6 to rotate along its central axis, the part 6 is a titanium alloy rod or tube, and the base 1 fixes and drives the titanium alloy rod or tube from both ends through the rotating shaft 2, a heating sleeve 3 is arranged around the metal part 6, and a channel 4 is processed on the heating sleeve 3 for inputting gradient materials 5 of different phases and process gases, the channel 4 is connected to the atmosphere, and the gap between the inner wall of the heating sleeve 3 and the outer surface of the metal part 6 is 1 / 3 to 1 / 2 of the maximum rotation radius of the metal part 6;

[0031] The steps of the preparation method are as follows:

[0032] Step 1: Preparation of metal parts 6 and gradient material 5

[0033] The metal part 6 is a titanium alloy rod or tube, and the surface of the metal part 6 is machined to make its surface roughness not greater than 1.6; Cr powder, Ti powder, Mg powder, Ni powder and Cu powder are prepared as gradient material 5, and the metal powder particle size is -350 mesh to -450 mesh, and the purity is 99.99%; hydrogen and helium are prepared as process gases, and the gas purity is 99.99%;

[0034] Step 2: Preheating of metal parts 6

[0035] Start the heating sleeve 3, raise the temperature to 500-700°C, and preheat the metal part 6. The preheating makes the surface of the metal part 6 red and sticky. Combined with the low roughness of the surface of the metal part 6, favorable conditions are formed for the subsequent attachment and mechanical pinning of the gradient material 5 on the low-smoothness surface of the metal part 6. At the same time, the metal part 6 starts to rotate at a speed of 10-20rad / s. This high speed of rotation can ensure that the temperature field of the metal part 6 is more uniform. The metal part 6 starts to keep warm while rotating, and the insulation time is 1h-2h. Then the rotation speed is reduced to 5-10rad / s. This speed makes the tangential speed of the gradient material 5 on the surface of the metal part 6 lower when it is attached and mechanically pinned, and prepares for the subsequent laying of the gradient material 5 powder;

[0036] Step 3: Laying the first layer of gradient material 5

[0037] The rotation speed of the metal part 6 is maintained, and Cr powder is sprayed onto the surface of the metal part 6 through the channel 4 at a spray rate of 70-100 mm / s. At this time, the Cr powder particles impact the surface of the metal part 6 at a relatively high speed and are pinned and fixed. When the Cr powder is laid to a thickness of 0.5-1.5 mm, the spraying is stopped, and the heating is stopped at the same time. The rotation speed of the metal part 6 is reduced to 1-5 rad / s, and helium is input into the heating sleeve 3 through the channel 4 to help the metal part 6 cool down. After that, the rotation speed of the metal part 6 is increased by 0.5-1 rad / s for every 50°C decrease in the temperature in the heating sleeve 3 until it is reduced to room temperature. During this process, the metal part 6 and the Cr powder layer on its surface shrink, causing the Cr powder particles that are not firmly pinned to fall off. In the process of increasing the rotation speed, the Cr powder particles that are not firmly pinned to fall off further, thereby preparing for the next secondary pinning operation;

[0038] After the temperature of the metal part 6 drops to room temperature, check the thickness of the Cr powder layer, and repeat the above operation process again until the Cr powder laying thickness reaches 0.5-1.5mm after the metal part 6 cools to room temperature;

[0039] Step 4: Solidification of the first layer of gradient material 5

[0040] The heating jacket 3 is started, and the temperature is raised to 600-1200°C, and the Cr powder layer on the surface of the metal part 6 is plasma sintered. At the same time, hydrogen is transported into the heating jacket 3 through the channel 4 at a pressure of 2-3 atmospheres. After the hydrogenation process is maintained for 0.5-1h, the metal part 6 is cooled to room temperature, and the pressure of the heating jacket 3 is restored to the atmospheric pressure level. At this time, the Cr powder layer has a porosity of 20-30%;

[0041] Step 5: Laying and curing the second to fifth layers of gradient material 5

[0042] Repeat steps 3 to 4 to sequentially complete the laying and solidification of Ti powder, Mg powder, Ni powder, and Cu powder, and then sequentially form a Cr-Ti-Mg-Ni-Cu heterogeneous layered structure on the surface of the metal part 6, wherein the layers of the layered structure have transition phases that intersect and adhere to each other;

[0043] Step 6: Heterogeneous layered structure deformation

[0044] An electric pulse power source is connected to both ends of the metal part 6 to heat the metal part 6 to 800-1200°C for plasma sintering. At the same time, the metal part 6 starts to rotate at a speed of 5-10 rad / s for 2-4 hours, and argon gas is supplied into the heating sleeve 3 at a pressure of 5-10 atmospheres. After dehydrogenation, the rotation and heating are stopped and the metal part is cooled to room temperature to obtain a titanium alloy rod or tube having a non-homogeneous gradient material Cr-Ti-Mg-Ni-Cu on the surface, and the microstructure is nano-sized and the grain boundaries are broken.

Claims

1. A method for preparing a heterogeneous gradient material, characterized in that: The device for use of the method comprises a base (1) having a supporting function, wherein the base (1) fixes a metal part (6) via a rotating shaft (2) and can drive the metal part (6) to rotate along its central axis, a heating sleeve (3) is arranged around the metal part (6), a channel (4) is processed on the heating sleeve (3) for inputting gradient materials (5) of different physical phases and process gas, the channel (4) is connected to the atmosphere, and the gap between the inner wall of the heating sleeve (3) and the outer surface of the metal part (6) is 1 / 3 to 1 / 2 of the maximum rotation radius of the metal part (6); The steps of the preparation method are as follows: Step 1: Preparation of metal parts (6) and gradient materials (5) The metal part (6) is a titanium alloy rod or tube, and the surface of the metal part (6) is machined so that its surface roughness is not greater than 1.6; Cr powder, Ti powder, Mg powder, Ni powder and Cu powder are prepared as gradient materials (5), and the metal powder particle size is -350 mesh to -450 mesh, and the purity is 99.99%; hydrogen and helium are prepared as process gases, and the gas purity is 99.99%; Step 2: Preheating of metal parts (6) The heating jacket (3) is started, and the temperature is raised to 500-700° C. to preheat the metal part (6), and at the same time, the metal part (6) starts to rotate at a speed of 10-20 rad / s. The metal part (6) starts to be kept warm while rotating, and the heat preservation time is 1h-2h, and then the rotation speed is reduced to 5-10 rad / s; Step 3: Laying the first layer of gradient material (5) The rotation speed of the metal part (6) is maintained, and Cr powder is sprayed onto the surface of the metal part (6) through the channel (4), with a spraying rate of 70-100 mm / s. At this time, the Cr powder particles impact the surface of the metal part (6) at a relatively high speed and are pinned and fixed. When the Cr powder is laid to a thickness of 0.5-1.5 mm, the spraying is stopped, and the heating is stopped at the same time. The rotation speed of the metal part (6) is reduced to 1-5 rad / s, and helium is input into the heating sleeve (3) through the channel (4) to help the metal part (6) cool. After that, the rotation speed of the metal part (6) is increased by 0.5-1 rad / s for every 50°C decrease in the temperature in the heating sleeve (3) until it is reduced to room temperature. During this process, the metal part (6) and the Cr powder layer on its surface shrink, causing the Cr powder particles that are not firmly pinned to fall off. In the process of increasing the rotation speed, the Cr powder particles that are not firmly pinned to fall off, thereby preparing for the next secondary pinning operation. After the temperature of the metal part (6) drops to room temperature, check the thickness of the Cr powder layer, and repeat the above operation process again until the thickness of the Cr powder layer reaches 0.5-1.5 mm after the metal part (6) cools to room temperature; Step 4: Solidification of the first layer of gradient material (5) The heating jacket (3) is started, and the temperature is raised to 600-1200° C., and the Cr powder layer on the surface of the metal part (6) is plasma sintered. At the same time, hydrogen is transported into the heating jacket (3) through the channel (4) at a pressure of 2-3 atmospheres. After the hydrogenation process is maintained for 0.5-1 hour, the metal part (6) is cooled to room temperature, and the pressure of the heating jacket (3) is restored to the atmospheric pressure level. At this time, the Cr powder layer has a porosity of 20-30%; Step 5: Laying and curing the second to fifth layers of gradient material (5) Repeating steps 3 to 4, the Ti powder, Mg powder, Ni powder, and Cu powder are laid and solidified in sequence, and then a Cr-Ti-Mg-Ni-Cu heterogeneous layered structure is formed on the surface of the metal part (6), wherein the layers of the layered structure have transition phases that intersect and adhere to each other; Step 6: Heterogeneous layered structure deformation An electric pulse power source is connected to both ends of the metal part (6) to heat the metal part (6) to 800-1200°C for plasma sintering. At the same time, the metal part (6) starts to rotate at a speed of 5-10 rad / s for 2-4 hours, and argon gas is supplied into the heating sleeve (3) at a pressure of 5-10 atmospheres. After dehydrogenation, the rotation and heating are stopped and the metal part is cooled to room temperature. Thus, a titanium alloy rod or tube having a surface with a non-homogeneous gradient material Cr-Ti-Mg-Ni-Cu can be obtained, and the microstructure is nano-sized and the grain boundary is broken.

2. The method for preparing a heterogeneous gradient material according to claim 1, characterized in that: The part (6) is a titanium alloy bar or tube.

3. The method for preparing a heterogeneous gradient material according to claim 2, characterized in that: The base (1) is fixed at both ends of a titanium alloy rod or tube through a rotating shaft (2) and drives the rod or tube to rotate.